Case report: Paternal uniparental disomy on chromosome 7 and homozygous SUGCT mutation in a fetus with overweight after birth - Bu, Xiufen; Li, Xu; Peng, Can; Li, Hongyu; Zhou, Shihao; Zhu, Zesen; He, Jun; Linpeng, Siyuan (Frontiers in Genetics, 2023)
Background: Paternal uniparental disomy (UPD) of chromosome 7 is extremely rare, and only a few postnatal cases have been reported. The effects on growth were discordant in these cases, and the relevance of paternal UPD(7) to growth caused by imprinting remains questionable.Case presentation: Here, we report a prenatal case that underwent invasive prenatal diagnosis due to the high risk of Down's syndrome and failed noninvasive prenatal screening. The fetus had a normal karyotype and no apparent copy number variation. Homozygous copy-neutral regions on chromosome 7 were identified using a single nucleotide polymorphism (SNP) array; the data for the parent-child trios showed that the fetus carried the whole paternal isodisomy of chromosome 7.Whole exome and Sanger sequencing revealed a homozygous frameshift mutation in SUGCT at 7p14.1, from the heterozygous carrier father, with no contribution from the mother. The parents decided to continue with the pregnancy after genetic counseling, and the neonate had normal physical findings at birth and showed overweight after birth during a long-term intensive follow-up.We report the first prenatal case who carried paternal UPD(7) and homozygous SUGCT mutation with an overweight phenotype after birth. The overweight may be caused by paternal UPD(7) or homozygous frameshift mutation of SUGCT, or both of them, but it is unclear which contributes more.